Аналіз методів просування іміджу бренду - Кітченко, Олена Миколаївна; Кучіна, Світлана Едуардівна (НТУ "ХПІ", 2017)
У статті розглядаються питання пов’язані з перспективами використання інтернет-брендингу, як одного з напрямів маркетингових комунікацій. Досліджується та ідентифікується поняття брендингу, його різновидів. Особлива увага приділяється розгляду поняття ко-брендингу. Описуються особливості застосування антибрендингу та надаються приклади його використання. Наголошується на необхідності розкрутки бренду з використанням можливостей Інтернет.

The article discusses issues related to the prospects of using Internet branding as one of the areas of marketing communications. The methods of brand promotion in different spheres of business are described. The concept of branding and its varieties is explored and identified. Particular attention is paid to the concept of co-branding, its features and principles of implementation. Attention is paid to new areas of brand promotion: touch branding, aroma branding, audio-branding. Features of using anti-branding are described and examples of its use are given. The concept of social responsibility of enterprises for the created products is considered. Examples of the concept of social responsibility in the modern world are given. The emphasis is on the need to promote the brand using the Internet, which is an effective condition for the promotion of the brand. The advantages and disadvantages of Internet branding are given.
Analysis of methods for promoting the brand image
Keywords: брендинг; ко-брендинг; антибрендинг; Інтернет; маркетинг; маркетинг відносин; споживачі; branding; co-branding; anti-branding; Internet; marketing; relationship marketing; consumers